A New Aspect of the TrkB Signaling Pathway in Neural Plasticity - Ohira, K (Bentham Science Publishers Ltd., 2009)
In the central nervous system (CNS), the expression of molecules is strictly regulated during development. Control of the spatiotemporal expression of molecules is a mechanism not only to construct the functional neuronal network but also to adjust the network in response to new information from outside of the individual, i.e., through learning and memory. Among the functional molecules in the CNS, one of the best-studied groups is the neurotrophins, which are nerve growth factor (NGF)-related gene family molecules. Neurotrophins include NGF, brain-derived neurotrophic factor (BDNF), neurotrophin 3 (NT-3), and NT-4/5 in the mammal. Among neurotrophins and their receptors, BDNF and tropomyosin-related kinases B (TrkB) are enriched in the CNS. In the CNS, the BDNF-TrkB signaling pathway fulfills a wide variety of functions throughout life, such as cell survival, migration, outgrowth of axons and dendrites, synaptogenesis, synaptic transmission, and remodeling of synapses. Although the same ligand and receptor, BDNF and TrkB, act in these various developmental events, we do not yet understand what kind of mechanism provokes the functional multiplicity of the BDNF-TrkB signaling pathway. In this review, we discuss the mechanism that elicits the variety of functions performed by the BDNF-TrkB signaling pathway in the CNS as a tool of pharmacological therapy.